Three-dimensional finite element analysis for structural parameters of asphalt pavement: A combined laboratory and field accelerated testing approach - Zhen Liu; Xingyu Gu; Hua Ren; Xiang Wang; Qiao Dong (Case Studies in Construction Materials, 2022)
To solve the issues that material parameters measured under specific laboratory conditions are extremely different from the actual pavement, a method of structural parameters correction in semi-rigid base asphalt pavement combining numerical simulations, laboratory tests, and accelerated pavement testing (APT) was proposed. The dynamic modulus and the uniaxial static compression creep tests were conducted to explore the effect of temperature, size, and fatigue. Then, these factors were coupled to the modified Burgers model that can reflect the creep law of the whole process. A constitutive model reflecting the real parameters of the pavement was subsequently constructed with the ABAQUS user-defined material (UMAT) subroutine. Experimental results illustrated it was verified that the modified subroutine has good feasibility both in single-layer and multi-layer materials from the actual pavement. Furthermore, simulated results also showed excellent agreement with field-tested findings. Finally, the rutting deformation curves and the demarcation points of each stage were obtained, which could guide the rutting prediction and maintenance decision of semi-rigid asphalt pavement.